First detection of Enterocytozoon bieneusi in whooper swans (Cygnus cygnus) in China - Wang, Yuexin (Parasit Vectors, 2020)
BACKGROUND: Enterocytozoon bieneusi is a parasite that infects humans and a wide range of other animals. The large migratory waterfowl, the whooper swan (Cygnus cygnus), travels through many cities during its migration and can spread parasites. Despite receiving increasing attention worldwide, there have been no reports of E. bieneusi infection occurring in C. cygnus. Therefore, this study aims to assess the prevalence and genetic characteristics of E. bieneusi in C. cygnus in Sanmenxia, China. METHODS: Altogether, 467 fresh fecal samples were collected in the Swan Wetland Park in Sanmenxia, China. Genomic DNA was extracted from fresh fecal samples (n = 467) and E. bieneusi was identified by nested PCR amplification of the internal transcribed spacer (ITS) region. ITS-positive sequences were aligned and phylogenetically analyzed to determine the genotypes of E. bieneusi. RESULTS: The overall prevalence of E. bieneusi in C. cygnus was 7.49% (35/467). Sequencing of the 35 positive samples revealed eight known genotypes (EbpA, EbpC, Henan-III, Henan-IV, BEB6, CD9, Peru6 and PtEb IX) and three novel genotypes (CSW1, CSW2 and CSW3). The phylogenetic tree constructed from the ITS sequences showed that seven genotypes (Peru6, EbpA, EbpC, Henan-III, CSW3, Henan-IV and CSW1) clustered within the zoonotic Group 1 while the remaining novel genotype CSW2 clustered within Group 5. CONCLUSIONS: To our knowledge, this is the first report of E. bieneusi in C. cygnus. Of public health significance, our results suggest that migratory C. cygnus might play an important role in the water-borne transmission of E. bieneusi. Effective strategies will be necessary to control E. bieneusi infection in C. cygnus, other animals and humans. [Image: see text]